OPTIMASI MAGNETIT TERSALUT ASAM HUMAT (Fe3O4-AH) SEBAGAI ADSORBEN METHYLENE BLUE - Rusda Vera Anggraini; Soerja Koesnarpadi; Nanang Tri Widodo (PROSIDING SEMINAR KIMIA, 2022)
Optimization of pH and contact time on the adsorption of methylene blue by magnetite coated with humic acid (Fe3O4-HA) using the batch method was studied. The synthesis of magnetite coated humic acid (Fe3O4-HA) was carried out by coprecipitation method with a ratio of 1:2 (w/w). Optimization of pH and contact time of magnetite coated humic acid (Fe3O4-HA) was carried out with 30 ppm methylene blue concentration and 0.1 g Fe3O4-HA mass. The optimum pH and optimum contact time of magnetite coated humic acid (Fe3O4-HA) were at pH 7 with adsorption percent of 99,93% and 120 minutes with adsorption percent of 93,88%. Keywords: Adsorption, Fe3O4-HA, Methylene Blue, Optimization